Total organic carbon from loss-on-ignition in lake sediments: accuracy of the method and implications for organic carbon burial estimates - Justine Frison; Hélène Masclaux; Loïc Angonin; Valentin Essert; Christophe Loup; Damien Rius; Laurent Millet (Journal of Paleolimnology, 2026)
In the context of ongoing climate change, understanding the global carbon cycle, especially the role of aquatic systems, is a major scientific challenge. Inland water bodies can act as sources or sinks of greenhouse gases, depending on their internal characteristics and the influence of external factors. Current global estimates of organic carbon accumulation rate (OCAR) in inland water bodies are mostly based on the reuse of available paleolimnological data. These estimates are mainly derived from total organic carbon (TOC) values converted from loss-on-ignition at 550 °C (LOI), using the LOI:TOC conversion factor established by Dean (1974). Our study focuses on the LOI:TOC relationship, based on 1,324 observations of lacustrine sediment samples derived from a broad typological gradient of sites (n = 465). Linear regression analysis revealed a strong relationship between LOI and TOC (TOC = LOI/2.27; R 2 = 0.79; p < 0.05). However, the predictive model provides estimates that differ distinctly from measured elemental TOC, especially at low LOI values. Change point analysis, based on the mean and variance of the LOI:TOC, suggests that the relationship is strong for LOI values greater than 15% (R 2 = 0.6, p < 0.05). However, the conversion factor leads to noticeable predictive errors for LOI values below 8.9% (R 2 = 0.25). These results suggest that the accuracy of the LOI:TOC relationship depends on the proportion of organic matter (OM). Furthermore, investigating the sediment composition, including elemental and CN ratios, of two sediment cores (Abbaye Lake and Mont-Coua Lake) suggested that the mineral composition of sediments, and the nature of OM significantly influence the LOI:TOC relationship, as demonstrated by previous studies. Newly defined conversion factors were used to calculate OCAR in both sediment records, and the associated errors were determined using the uncertainty propagation method. OCAR derived from LOI-based TOC can have errors up to three times greater than those based on measured elemental TOC. Our results suggest that indirect TOC measurement through LOI can lead to biased OCAR results depending on multiple interrelated sedimentary factors specific to inland water bodies, shaped by their ecological functioning and environmental drivers. Direct TOC measurement should therefore be prioritised in global OCAR estimates.

Assessment of carbon isotopic signature of Daphnia ephippia as a proxy for past carbon transfers to pelagic food webs in Jura lakes - Valentin Essert; Laurent Millet; Valérie Verneaux; Jules Millet; Hélène Masclaux (Journal of Paleolimnology, 2023)

Origin and fate of dissolved inorganic carbon in a karst groundwater fed peatland using δ13CDIC - Alexandre Lhosmot; Marc Steinmann; Philippe Binet; Laure Gandois; Jean-Sébastien Moquet; Vanessa Stefani; Marie-Laure Toussaint; Anne Boetsch; Christophe Loup; Valentin Essert; Guillaume Bertrand (Chemical Geology, 2023)